A survey of how patient-perceived empathy affects the relationship between health literacy and the understanding of information by orthopedic patients? - Chu Cheng-I; Tseng Chia-Chih (BMC, 2013)
Abstract Background There is a lack of research examining patient-perceived empathy and its effect on low-literacy patients' understanding of health information. This study investigated the moderating effect of patient-perceived empathy on the relationship between health literacy and understanding of preoperative information. Methods During a 2-month period, a total of 144 patients took a survey that included the Chinese-edition Rapid Estimate of Adult Literacy in Medicine, the Barrett-Lennard Relationship Inventory and the Preoperative Information Understanding Scale. Hierarchical multiple regression analysis provided a test of moderator effects. Results All Cronbach's alphas exceeded 0.6, with REALM at 0.91, BLRI at 0.67, and PIUS at 0.77.The finding that the interaction term was significant suggests perceived empathy is a relevant factor when considering the relationship between health literacy and the understanding of information by patients. The relationship between the health literacy and understanding of information was stronger and positive among patients who perceived greater empathy from their physicians. Conclusion Our study demonstrates that a focus on improving physician-patient empathy skills could be beneficial in helping to overcome the negative consequences associated with limited health-literacy capabilities. Healthcare providers who wish to improve the understanding of information by low health-literacy patients should first identify components of their empathic communication mechanisms, and then try to refine these skills to better serve their patients.